2017
DOI: 10.1136/bmjresp-2017-000215
|View full text |Cite
|
Sign up to set email alerts
|

London ambulance source data on choking incidence for the calendar year 2016: an observational study

Abstract: IntroductionComplete foreign body airway obstruction is a life-threatening emergency, but there are limited data on its epidemiology.MethodsWe conducted a retrospective analysis of data collected routinely from London Ambulance Service calls coded as being for choking was undertaken for the calendar year of 2016.ResultsThere were 1916 choking episodes of significant severity to call for emergency assessment in London during 2016, 0.2% of total calls requiring an ambulance response, an average of 5.2 per day. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 13 publications
2
23
0
Order By: Relevance
“…14 In Osaka Prefecture, it was reported that 24.5% of out-of-hospital cardiac arrests from choking on rice cake occurred during the first 3 days of the New Year. 8 A high incidence of choking among older people is consistent with results of studies conducted in the United States, 15 , 16 the United Kingdom, 17 Australia, 18 and Taiwan. 19 However, seasonal variations, such as Japan’s high frequency of deaths in January, were not observed in the United Kingdom study, 17 possibly attributable to the Japanese tradition of eating rice cake to celebrate the New Year.…”
Section: Discussionsupporting
confidence: 81%
“…14 In Osaka Prefecture, it was reported that 24.5% of out-of-hospital cardiac arrests from choking on rice cake occurred during the first 3 days of the New Year. 8 A high incidence of choking among older people is consistent with results of studies conducted in the United States, 15 , 16 the United Kingdom, 17 Australia, 18 and Taiwan. 19 However, seasonal variations, such as Japan’s high frequency of deaths in January, were not observed in the United Kingdom study, 17 possibly attributable to the Japanese tradition of eating rice cake to celebrate the New Year.…”
Section: Discussionsupporting
confidence: 81%
“…Babies during the Covid-19 Pandemic had an impact on choking management skills in infants. The baby was associated with increased risk of choking and the highest frequency of choking on finger foods occurred in those who were given finger foods the least often [15][16][17] . This shows that the education provided can be used as a preventive in management efforts if choking occurs in infants 18,19 .…”
Section: Based On the Results Of The Study It Was Found That Audio-visual Education On Lactation Management And Management Of Choking Babmentioning
confidence: 99%
“…Causes of FBAO FBAO usually occurs while the casualty is eating or drinking and can be associated with muscle, neurological or cerebral impairment. 6 Most deaths from choking are caused by food (87%); while small objects, a particular cause in children, are the cause of 13% of choking related deaths. 1 People at increased risk of FBAO include those with altered level of consciousness, drug and/or alcohol intoxication, neurological impairment with reduced swallowing and cough reflexes (for example, stroke, Parkinson's disease), respiratory disease, mental impairment, dementia, poor dentition, and the elderly.…”
Section: The Medicines and Healthcare Productsmentioning
confidence: 99%
“…5 In London alone, there are close to 2,000 FBAO episodes each year of significant severity requiring the need to call 999 for an ambulance. 6 In adults, the incidence of FBAO increases with age. 7 Deaths from FBAO are more common in older people with almost 30% of deaths associated with FBAO occurring in the 80 years and over age group.…”
mentioning
confidence: 99%